Assessing the relationship between a web application-based load and recovery score and training load, considering the menstrual cycle: A longitudinal observational study in elite women’s soccer - Stefanie L. Brefin; Jan Anderegg; Claudio R. Nigg; David Koschnick; Claudia Paul; Sascha Ketelhut (Current Issues in Sport Science, 2024)
Introduction